Associations of serum 25(OH)D levels with physical performance and anabolic hormones in young men - Laaksi, Akseli; Laaksi, Ilkka; Pihlajamäki, Harri; Vaara, Jani P.; Luukkaala, Tiina; Kyröläinen, Heikki (Frontiers in Physiology, 2023)
Purpose: The present study examined the association of vitamin D measured by serum 25(OH)D with physical performance outcomes and serum levels of anabolic hormones in young men. Methods: 412 young men (age 19 ± 1 years) entering their compulsory military service volunteered to participate in the study. The study consisted of two groups from two different military bases: Group A was studied in January and group B in July. The groups were first compared with each other and due to statistically significant (p<0.001 analyzed with independent samples t-test) differences in physical condition (sit-up, push-up, and standing long jump-tests and testosterone levels) between the groups, groups were analyzed separately. The serum levels of 25(OH)D, testosterone (TES), sex hormone binding globulin (SHBG), and insulin-like growth factor-1 (IGF-1) were analyzed by electrochemiluminescence immunoassay. Physical performance tests consisted of muscular fitness (sit-ups, push-ups, standing long jump) and aerobic fitness (12-minute-running) tests. The association of serum 25(OH)D with physical performance tests and anabolic hormones was analyzed using linear regression. Results: After controlling for the group, body mass index, and leisure-time physical activity, serum 25(OH)D level was positively associated with aerobic and muscular fitness (β= 0.15 – 0.20, all p<0.05). Also, the participants with sufficient serum 25(OH)D levels (75 nmol/l) had better aerobic and muscular fitness and higher TES in group B, and better upper extremity muscular fitness in group A (all p<0.05). In group A, there were 166 participants with serum levels of 25(OH)D <75nmol/l and 18 75nmol/l. In group B, the amounts were 92 (<75nmol/l) and 136 (75nmol/l), respectively. Conclusions: Serum 25(OH)D was positively associated with both aerobic and muscular fitness and those with sufficient vitamin D levels, had higher levels of TES. Thus, maintaining a sufficient serum 25(OH)D level may be beneficial for physical performance and anabolic state in young men.